Pengaruh Tingkat Inflasi, Suku Bunga Kredit Konsumsi, dan Dana Pihak Ketiga (DPK) terhadap Kredit Konsumsi Bank Umum di Indonesia, 2004-2008 - Nunik Kadarwati; Oke Setiarso (EKO-REGIONAL, 2011)
It aims to find out the influence of inflation rate, interest rate, consumption credit interest, and third party fund toward consumption credit of banks in Indonesia partially and simultaneously, and also to find out a variable which has biggest influence on consumption credit of banks in Indonesia.Research result shows inflation rate, consumption credit interest, and third party fund (clearing account, saving, and fixed deposit) significantly influence consumption credit of banks in Indonesia 2004-2008 period partially and simultaneously, and consumption credit interest has the biggest influence. Implications of this research are in order to keep the increasing of consumption credit, Bank Indonesia should keep inflation rate, consumption credit interest, clearing account, saving, and fixed deposit carefully to keep the stability thus have good impact to economic growth in Indonesia. Keywords: inflation, interest rate, consumption credit